Acute Acalculous Cholecystitis due to Viral Hepatitis A - Safak Kaya; Ahmet Emre Eskazan; Nurettin Ay; Birol Baysal; Mehmet Veysi Bahadir; Arzu Onur; Recai Duymus (Case Reports in Infectious Diseases)
Inflammation of the gallbladder without evidence of calculi is known as acute acalculous cholecystitis (AAC). AAC is frequently associated with gangrene, perforation, and empyema. Due to these associated complications, AAC can be associated with high morbidity and mortality. Medical or surgical treatments can be chosen according to the general condition of the patient, underlying disease and agent. Particularly in acute acalculous cholecystitis cases, early diagnosis and early medical treatment have a positive effect on the patient and protect them from surgical trauma. ACC is a rare complication of acute viral hepatitis A. Herein, we present an adult patient of acalculous cholecystitis due to acute viral hepatitis A. She responded to the conservative management.